Efektivitas Art Therapy Untuk Pasien dengan General Anxiety Disorder(GAD) - Nagara, Angga Dipa; Rifa’i, M. Ridwan (Karsa Husada Health Institute Garut, 2020)
The presence of Anxiety Disorder is associated with a lower quality of life (quality of life) and a negative impact on psychosocial functioning. The combination of psycho therapy with CBT is recommended but about 50% of individuals with IK are not benefiting from CBT or would rather not take medication or prefer non-verbal therapy individuals may benefit from Art Therapy. The aim of this paper is to see how effective Art Therapy is for patients with Anxiety Disorders. The process of searching for articles using the PubMed, ScienceDirect, and DOAJ databases with the keywords